Modern Communication Culture and Working among Teachers in Bangkok Metropolis - ผิวนิล, นายฐิตินันทน์ (Journal of Digital Communications, 2017)
The objective of this study is to explore the relationship between personal characteristics, knowledge, attitudes, meanings, and value of online communication and online communication culture of the teachers in schools under the governance of Department of Education BMA. This study adopted both quantitative and qualitative methods by utilizing questionnaire survey and group and in-depth interviews. The sample group comprises 641 teachers from 44 schools under the governance of Department of Education BMA. The study was conducted from April to August 2017. The key informants of both interviews consists of 20 teachers and school executives from 10 schools. The findings revealed that 50.1 percent of teachers own a smartphone. Their level of knowledge of using online communication for teaching and learning is high. They have pretty good attitude toward using communication technology for teaching and learning. They also see that online communication media helps them receive news and information as well as work faster and more conveniently. The statistically significant important factors relevant to teachers’ online communication are age, income, knowledge, skill, attitude, ownership of communication equipment, and policy awareness. This study, therefore, supports schools under the administration of Department of Education BMA to apply online communication in learning and teaching and simultaneously to promote the appropriate use of online communication for students by providing both knowledge and better utilization of online communication.